The Impact of Land Cover Change in the Bolon Watershed on Flood Zonation - Pane, Indah Permatasari Br. S.; Mardianta, Anthoni Veery; Mulia, Ahmad Perwira (Journal La Lifesci, 2025)
Flood risk assessment plays a crucial role in determining flood hazard zones and formulating effective mitigation strategies. Using a multi- criteria decision support system, this study focuses on evaluating the flood risk index within the Bolon Watershed (DAS Bolon). Geographic Information Systems (GIS) were employed as an effective disaster mitigation tool to provide comprehensive geospatial data. The research integrates the Cellular Automata–Markov Chain (CA–MC) model using the MOLUSCE plugin in QGIS to spatially project land-use change analysis, the Analytical Hierarchy Process (AHP) to determine variable weights influencing flood risk, and Weighted Multi-Criteria Analysis (WMCA) for spatial flood zonation assessment. Between 2017 and 2021, significant land-cover changes occurred in the Bolon Watershed, with 67.55 km² converted into residential areas. Forest Flood risk assessment plays a crucial role in determining flood hazard zones and formulating effective mitigation strategies. Using a multi- criteria decision support system, this study focuses on evaluating the flood risk index within the Bolon Watershed (DAS Bolon). Geographic Information Systems (GIS) were employed as an effective disaster mitigation tool to provide comprehensive geospatial data. The research integrates the Cellular Automata–Markov Chain (CA–MC) model using the MOLUSCE plugin in QGIS to spatially project land-use change analysis, the Analytical Hierarchy Process (AHP) to determine variable weights influencing flood risk, and Weighted Multi-Criteria Analysis (WMCA) for spatial flood zonation assessment. Between 2017 and 2021, significant land-cover changes occurred in the Bolon Watershed, with 67.55 km² converted into residential areas. Forest deforestation began in 2017 and is projected to continue until 2033, potentially disrupting the hydrological cycle and intensifying flood-prone zones. As a result, the flood-prone residential area increased markedly from 1.4% (2017) to 2.89% (2021) and is projected to reach 4.74% by 2033, with an average annual increase of 0.21%. This study underscores the importance of improved land-cover management to mitigate flood zonation in the Bolon Watershed. It also emphasizes the need for strict enforcement of spatial planning and zoning regulations, as well as enhanced monitoring and legal measures against land-use conversion particularly in flood-prone and water recharge areas